The spiny dogfish ('cacao-bagre'): description of an envenoming in a fisherman, with taxonomic and toxinologic comments on the Squalus gender - Haddad, V; Gadig, OBF (Elsevier B.V., 2005)
The authors report an injury caused by a spiny dogfish (Squalus sp) in a professional fisherman that was got hurt in the left hand for a spine in the dorsal fin of the fish and felt excruciating local pain for 6 h and manifested local edema and erythema. The sharks of the Squalus gender, in a similar way to the gender Heterodontus, present two spines in position previous to the dorsal fins, with channels presenting a whitish mass, composed of great and vacuolated cells that produce venom. The Squalus gender has a complex taxonomy, with five nominal species mentioned in Brazil: S. acanthias, S., blainvillei, S. cubensis, S. megalops and S. mitsukurii. The species associated to the injury belongs to the group 'megalops/cubensis'. A detailed study on the taxonomy and toxinology of the Squalus gender in Brazil would be of vital importance in the resolution of those problems and it would serve as subsidy for any other works involving their representatives, besides with aspects of envenoming that this gender can cause and that has rare citations in the literature. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: venomous fishes; venoms; Squalus; spiny dogfish; sharks